2016
DOI: 10.1097/hp.0000000000000499
|View full text |Cite
|
Sign up to set email alerts
|

Acute Radiation Syndrome Severity Score System in Mouse Total-Body Irradiation Model

Abstract: Radiation accidents or terrorist attacks can result in serious consequences for the civilian population and for military personnel responding to such emergencies. The early medical management situation requires quantitative indications for early initiation of cytokine therapy in individuals exposed to life-threatening radiation doses and effective triage tools for first responders in mass-casualty radiological incidents. Previously established animal (Mus musculus, Macaca mulatta) total-body irradiation (γ-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…13,14 Metabolomics based on mass spectrometry (MS) platforms has shown great potential to explore the biomarkers of radiation damage due to high-throughput and minimally invasive sample collection methods. 15,16 Over the last decade, metabolomics studies have been conducted using rodent, 17,18 non-human primates, 19,20 and humans 21,22 to explore IR-induced potential biomarkers. These studies have confirmed a large number of metabolites are altered after exposure to IR.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Metabolomics based on mass spectrometry (MS) platforms has shown great potential to explore the biomarkers of radiation damage due to high-throughput and minimally invasive sample collection methods. 15,16 Over the last decade, metabolomics studies have been conducted using rodent, 17,18 non-human primates, 19,20 and humans 21,22 to explore IR-induced potential biomarkers. These studies have confirmed a large number of metabolites are altered after exposure to IR.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have systematically validated radio-responsive human protein markers in vivo for dose- and time-response after radiation exposure. Radiation responsive plasma proteins such as Flt3 ligand (Flt3L), serum amyloid A (SAA) and Interleukin-6 (IL-6) have been studied in mouse models as markers of acute radiation syndrome and radiation exposure up to a week 10 , 11 . Using the NHP model, C-reactive protein (CRP), SAA, IL-6, Flt3L protein biomarkers expressed in NHP plasma have been proposed as early indicators of dose assessment and radiation-induced injury up to ~7 days post irradiation 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…However, single‐dose assessment is not sufficient to provide information on organ injury. Whole‐body or partial‐body irradiation with high doses can result in the acute radiation syndrome and multiple organ dysfunction syndrome (Ossetrova, Ney, Condliffe, Krasnopolsky, & Hieber, ; Roy et al, ), both of which are related to organ injury. In addition, radiation doses in the body are usually inhomogeneous in radiation accidents.…”
Section: Introductionmentioning
confidence: 99%